Cause-specific mortality in classic Kaposi's sarcoma: a population-based study in Italy (1995–2002) - Ascoli, V (Nature Publishing Group, 2009)
BACKGROUND: Little information is available on the causes of death among persons with classic Kaposi's sarcoma (CKS). METHODS: We conducted a population-based study in Italy to identify deceased persons with CKS and the underlying causes of death among them, by reviewing multiple-causes-of-death records. Standardised mortality ratios (SMRs) and 95% confidence intervals were calculated to compare the distribution of causes to that among the same-age general population of deceased persons. The geographical distribution was also evaluated. RESULTS: Of the 946 deaths among persons with CKS, 65.9% were attributable to non-neoplastic conditions and 21.9% to malignancies. For 12.2%, no lethal pathology was identified and CKS was considered as the underlying cause. In 90% of these cases, there was visceral/nodal involvement, therapy-related complications, or neoplastic cachexia. Among persons with CKS who died of other causes, an excess for lymphoid malignancies emerged (SMR=4.40) (chronic lymphocytic leukaemia (11.03), non-Hodgkin's lymphoma (4.22), Hodgkin's lymphoma (11.80), and multiple myeloma (2.3)), balanced by a deficit for all solid cancers (0.56), with a marked deficit for lung cancer (0.41). We found an excess for respiratory diseases (chronic obstructive pulmonary disease (1.86)) and genitourinary diseases (chronic renal failure (6.47)). There was marked geographical heterogeneity in the distribution of deaths. CONCLUSIONS: Though referring specifically to Italy, the results are informative for other countries and populations and all cases of CKS in general.